Antioxidant properties of infusions from leaves of sweet potato (Ipomoea batatas L. Lam) depending on temperature and brewing time - Barbara Krochmal-Marczak; Anna Kiełtyka-Dadasiewicz; Barbara Sawicka (Journal of Central European Agriculture, 2019)
Antioxidant activity of water infusions made from leaves of five sweet potato cultivars (Carmen Rubin, Georgia Jet, Beauguard, White Triumph and Satsumo Imo), originating from a field cultivation on brown and acidic soil (49°49'N 21°50'E) was determined by means of DPPH method. The field experiment was carried out using the randomized block method in triplicate. Leaves collected in the BBCH 68 phase, after drying, were brewed with water at a temperature of 80 and 100 ℃, for 2, 5 and 10 minutes. The antioxidant activity of infusions from sweet potato leaves was determined applying spectrophotometric method with the DPPH radical. Individual varieties differed in antioxidant activity: the highest was White Triumph (52-57%) and the lowest - Beauguard (45-53%). The infusions prepared at 100 °C were characterized by higher antioxidant activity (52-58%) compared to those prepared with the use of water at 80 °C (41-47%). The time of brewing preparation had a significant effect on antioxidant activity. Its highest value was recorded after 5 minutes, and the lowest after 2 minutes of brewing the dried sweet potato leaves